PENGARUH RASIO PROFITABILITAS, LIKUIDITAS DAN SOLVABILITAS TERHADAP PERTUMBUHAN LABA (Studi pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Irma Yuliani; Rizca Puspita Devi (Economicus, 2024)
This research aims to determine whether profitability ratios reviewed using the Return on Equity (ROE) formula, liquidity ratios reviewed using the Current Ratio (CR) formula and solvency ratios reviewed using the Debt to Equity Ratio (DER) formula have an effect on profit growth, in food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2022 period. In this research, data was obtained using the purposive sampling method. The results of the analysis in this study, which consisted of classical assumption tests, showed that there were no symptoms of multicollinearity, there were symptoms of autocorrelation which had been corrected through the runs test, there were no symptoms of heteroscedasticity, and the data used was normal. Then, from the results of the regression analysis, the data used shows that Return on Equity (ROE) X1 partially has a significant effect on profit growth with a significance value of 0.006. Meanwhile, the Current Ratio (CR) and Debt to Equity Ratio (DER) partially have no effect on profit growth. Simultaneously, Return on Equity Ratio (ROE), Current Ratio (CR) and Debt to Equity Ratio (DER) influence profit growth in a sample of food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2022 period.